A new analytical system, based on an acoustic wave sensor, for halitosis evaluation - Fernandes, Daniel L. A. (2009)
http://www.sciencedirect.com/science/article/B6THH-4TVJ3JY-5/2/0224559e18093438275068c97d11468c